A Quasi-Experimental Study of a Pharmacist-Led Community Educational Intervention on Medication Knowledge and Adherence among Older Adults with Chronic Illness in Surakarta - Risma Sakti Pambudi; Khotimatul Khusna; Ratih Sakti Prastiwi; Adi Wardhana Amrullah; Ulfah Nur Hanna; Meri Agustina (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Chronic diseases such as diabetes mellitus and hypertension are increasingly prevalent among older adults and require long-term medication use. Despite receiving routine health education in primary care, many patients continue to show gaps in medication knowledge and adherence, which can lead to poor treatment outcomes. Pharmacist-led education has the potential to address these gaps by combining professional guidance with behavioral reinforcement. This study aimed to evaluate the effectiveness of a community-based, interactive educational program in improving medication knowledge and adherence among older adults with chronic diseases. Methods: A quasi-experimental pretest–post-test design was conducted between June and August 2025 with 201 participants recruited from five primary health centers in Surakarta, Indonesia. Medication knowledge and adherence were assessed using a structured questionnaire administered before and after two pharmacist-led group education sessions. The educational sessions focused on proper medication use, lifestyle management, and strategies to reduce unintentional nonadherence. The questionnaire evaluated multiple domains of knowledge and self-reported adherence behaviors. Differences between pre- and post-intervention scores were analyzed using the Wilcoxon Signed-Rank test, with the level of statistical significance set at p < 0.05. Results: The Wilcoxon Signed-Rank test revealed statistically significant differences between pretest and post-test scores for both medication knowledge and adherence. Knowledge scores increased significantly following the intervention (Z= ?10.624, p < 0.05) indicating improved understanding of medication use and related health behaviors. Adherence scores also showed a significant increase (Z= ?9.767, p < 0.05). The greatest improvements were observed in lifestyle-related knowledge, such as diet and physiscal activity, as well as in behaviors associated with unintentional nonadherence, including forgetting doses or failing to bring medications while traveling. Minimal changes were observed in knowledge regarding diabetes-specific medications, showed minimal change, suggesting adequate baseline familiarity. Conclusion: The pharmacist-led community educational intervention was associated with statistically significant improvements in medication knowledge and adherence among older adults with chronic diseases. Further research is needed to assess the sustainability of these improvements over longer follow-up periods and across different primary healthcare settings.